The Proses pembuatan baut tarik beton menggunakan mesin bubut CNC - Fikri Fathurrahman, Fikri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
A CNC (Computer Numerical Controlled) machine is a machine tool which in the operation of the process of cutting (cutting) a workpiece by a chisel / cutting tool is assisted by numerical control using a computer. CAD (Computer-Aided Design) is a technology related to the use of computer systems to assist in the process of making, modifying, analyzing and optimizing designs. CAM (Computer-Aided Manufacturing) is the use of computer software to control machine tools or other machine parts related to the machining process. AutoCAD is a CAD (Computer Aided Design) program released by Autodesk. Basically CAD is a program for design, to be precise for designing or drawing techniques using a computer. Mastercam is software or software developed by CNC Software, Inc. from the United States, this software allows designing, then planning the manufacturing process through simulations both for lathes (turning) and milling (milling) which are carried out simultaneously. Concrete tensile bolts are components in rail bearing concrete that have a function as a concrete puller bearing so that it is parallel, this bolt has 2 parts that are combined, namely the bolt rod part made of VCN 150 steel and the bolt head nut made of SS 400 steel. Keywords: CNC machines, CAD / CAM, Autocad, Mastercam